Association of adiposity with pulmonary function in older Chinese: Guangzhou Biobank Cohort Study. (November 2017) - Pan, Jing; Xu, Lin; Lam, Tai Hing; Jiang, Chao Qiang; Zhang, Wei Sen; Jin, Ya Li; Zhu, Feng; Zhu, Tong; Thomas, G. Neil; Cheng, Kar Keung; Adab, Peymane
Abstract: Objective: We examined the association between different adiposity indices and pulmonary function in Chinese adults in the Guangzhou Biobank Cohort Study (GBCS). Methods: Participants with body mass index (BMI) < 18.5 (underweight) were excluded. Adiposity indices including BMI, waist circumference (WC), waist hip ratio, waist height ratio and body fat percentage were measured. Lung function was assessed by spirometry using a turbine flowmeter. We analyzed percent predicted for forced expiratory volume in 1 s (FEV1 %), forced vital capacity (FVC %) and restrictive respiratory defect (FEV1 /FVC ratio > low limits of normal and FVC % <0.80). Results: Of 16186 participants (mean age 61.4 ± 7.2 years; 74.0% women), 116 (0.7%) had only general obesity (BMI ≥28 kg/m 2 ), 4079 (25.2%) had only central obesity (WC: ≥90 cm in men, ≥80 cm in women) and 1591 (9.8%) had both central obesity and general obesity. Comparing to those with neither central nor general obesity, those with only central adiposity and with both central and general obesity had lower pulmonary function (adjusted β range from -2.85 to -6.02 for FEV1 % and FVC%, adjusted OR range from 1.14 to 1.70, all P < 0.05). But those with only general obesity had better but non-significant pulmonary function. (Crude β range from 1.46 to 2.92 for FEV1 % and FVC%, crude OR range from 0.68 to 0.93, all P > 0.05). Both FEV1 % and FVC% decreased per standard deviation increase in obesity indices (adjusted β from -0.46 to -3.17, all P < 0.002). A positive association of central or general obesity with restrictive respiratory defect was observed (adjusted odds ratio (AOR) from 1.50 to 2.04, all P < 0.002). Further adjustment for WC reversed the inverse association between BMI and pulmonary function (adjusted β from 1.93 to 6.22, all P < 0.001) and restrictive respiratory defect (adjusted AOR from 0.72 to 0.80, all P < 0.001). Conclusion: Central adiposity and its indices, but not general adiposity and BMI, were independently associated with lower pulmonary function and higher risk of restrictive respiratory defect in older Chinese. Highlights: Those with central obesity had lower lung function, independent of general obesity. Those with only general obesity had better but non-significant pulmonary function. General and central obesity indices inversely associated with lower lung function. Adjustment for WC reversed the inverse association between BMI and lung function. Central but not general obesity was independently associated with lower lung function.